Cerebral oximetry levels during CPR are associated with return of spontaneous circulation following cardiac arrest: an observational study. Issue 5 (24th March 2014) - Singer, Adam J; Ahn, Anna; Inigo-Santiago, Loren A; Thode, Henry C; Henry, Mark C; Parnia, Sam
Abstract : Objectives: Cerebral oximetry using near-infrared spectroscopy measures regional cerebral oxygen saturation (rSO2 ) non-invasively and may provide information regarding the quality of cerebral oxygen perfusion. We determined whether the level of rSO2 obtained during cardiopulmonary resuscitation is associated with return of spontaneous circulation (ROSC) and survival in Emergency Department (ED) patients presenting with cardiac arrest. Methods: We conducted a retrospective, observational study of adult ED patients presenting at an academic medical centre with cardiac arrest in whom continuous cerebral oximetry was performed. Demographic and clinical data including age, gender, presenting rhythm and mean rSO2 readings were abstracted. Cerebral oxygenation was measured with a commercially available oximeter. Results: A convenience study sample included 59 patients ages 18–102 years (mean age 68.7 ± 14.9 years); 50 (84.7%) were men. Presenting rhythms included pulseless electrical activity (21), asystole (20) and ventricular fibrillation/tachycardia (17). 24 patients (40.6%) had ROSC and only 1 (1.7%) survived to hospital discharge. Patients with and without ROSC were similar in age and presenting cardiac rhythms. The mean of mean rSO2 levels was higher in patients with ROSC, 43.8 (95% CI 40.1 to 47.6) compared with those without ROSC, 34.2 (95% CI 30.6 to 37.8); p=0.001. 91.7% of patients with ROSC had a rSO2 of 30% or greater compared with 62.9% in those without ROSC (p=0.01). The area under the curve for mean rSO2 as a predictor of ROSC was 0.76 (95% CI 0.64 to 0.89). Conclusions: In ED patients with cardiac arrest higher cerebral oxygen saturations are associated with higher rates of ROSC.